1994
DOI: 10.1136/hrt.72.2.197
|View full text |Cite
|
Sign up to set email alerts
|

New sex dependent normal limits of the signal averaged electrocardiogram.

Abstract: Background-An earlier study of 1555 normal 12 lead electrocardiograms has shown that the mean QRS duration in men is 8 ms longer than in women. Objective-To establish the sex related normal limits of the signal averaged electrocardiogram. Results-There were significant differences between the two sexes in QRS duration (mean (95% confidence interval (95% CI)) (8.0 (3.1 to 13*0) ms, t = 3-29, degrees of freedom = 41, p = 0-0021 with the 25-250Hz filter; mean (95% CI) 10-2 (6-9 to 13.5) ms, t = 6*26, degrees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Raineri, et al 5) reported that the difference between the sexes could be corrected by adjusting for height. Yang, et al 7) reported a strong correlation between fQRS and body surface area. Ozawa, et al 11) reported a difference fQRS values between the sexes and a correlation between fQRS values and body surface area in a Japanese cohort of SAE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raineri, et al 5) reported that the difference between the sexes could be corrected by adjusting for height. Yang, et al 7) reported a strong correlation between fQRS and body surface area. Ozawa, et al 11) reported a difference fQRS values between the sexes and a correlation between fQRS values and body surface area in a Japanese cohort of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that the diagnostic criteria between normal and abnormal SAE values and the late potentials of QRS vary, depending on the equipment used and how the filters are set. However, according to these reports, values determined from a 95% confidence interval of normal subjects [3][4][5][6][7] or determined standard values for comparison of myocardial infarction patients with and without ventricular tachycardia [8][9][10] those criteria varied. The difference in RMS 20 caused by (F) and (B) filter direction was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang and MacFarlane 7 found no specific age‐related change in normals between the ages of 40 and 69 years in any of the three SAECG parameters. Mercando et al compared SAECG data in 51 normal subjects, aged 62–102 years, with 25 asymptomatic volunteers under the age of 50 13 .…”
Section: What Are the Normal Values For Saecg?mentioning
confidence: 91%
“…However, it was not noted that the filtered fQRS duration may be different by gender. Over the past decade, there has been no modification of these normal values despite several published studies that indicate that there are gender‐related differences in the SAECG 3–8 …”
Section: What Are the Normal Values For Saecg?mentioning
confidence: 99%